Role of BDNF Signaling in Memory Enhancement Induced by Transcranial Direct Current Stimulation - Cocco, Sara; Podda, Maria V.; Grassi, Claudio (Frontiers in Neuroscience, 2018)
In the recent years numerous studies have provided encouraging results supporting the use of transcranial direct current stimulation (tDCS) as non-invasive brain stimulation technique to improve motor and cognitive functions in patients suffering from neurological and neuropsychiatric disorders as well as in healthy subjects. Among the multiple effects elicited by tDCS on cognitive functions, experimental evidence and clinical findings have highlighted the beneficial impact on long-term memory. Memory deficits occur during physiological aging as well as in neurological and neurodegenerative disorders, including Alzheimer’s disease. In this scenario, non-invasive techniques for memory enhancement, such as tDCS, are receiving increasing attention. The knowledge of molecular mechanisms subtending tDCS effects is of pivotal importance for a more rationale use of this technique in clinical settings. Although we are still far from having a clear picture, recent literature on human and animal studies has pointed to the involvement of synaptic plasticity mechanisms in mediating tDCS effects on long-term memory. Here we review these studies focusing on the neurotrophin BDNF as critical tDCS effector.